A Clinical Overview on Spondylitis (Homoeopathy for All, 2026)
Spondylitis refers to a group of inflammatory condition primarily affecting the joints of the spine and the sacroiliac region, comprising of the pelvis and the lower spine. It is derived from the combination of two Latin words namely “spondylo” which refers to “of the vertebrae” and “it is” which refers to inflammation. This condition is more prevalent in both males and females belonging to the age group of 20 to 40 years. It causes chronic pain and stiffness in the lower back and hips, neck pain and fatigue. Traditionally, there are 6 types of Spondylitis namely Ankylosing Spondylitis, Enteropathic Arthritis, Psoriatic arthritis, Reactive Arthritis or Reiter’s Syndrome, Juvenile Sponylitis and Undifferentiated Spondylitis
Keywords: Spondylitis; genetic predisposition; Undifferentiated Spondylitis; Enteropathic Arthritis